The biological role of clove oil in the diet of mature male rabbits on the physiological body functions, oxidative stress and physical semen properties - A. A. M. Habeeb; M. A. A. Atta; A. I. A. Elhanafy; A. K. Sharaf (Diponegoro University, 2023)
In an eight-week experiment conducted throughout the months of January and February, 2023, the goal of this study was to determine how changing the diet of mature male rabbits to include clove oil affected their body's physiological processes and the quality of their sperm. In this study, 24 mature rabbit bucks that were 8 months old and weighed an average of 2.650 g in the first production year were used. In a final randomized plan, the bucks were randomly assigned to two experimental groups, each with twelve rabbits. Bucks served as the control group in the first group and were fed a commercial pelleted food without any supplements. Each buck in the second group received one milliliter of clove along with the daily diet requirement from commercial pellets. Every two weeks, values for weight gain, feed consumption, testosterone levels, blood constituents, libido, and semen quality were assessed. The findings demonstrated that including clove oil in the diet of bucks rabbits resulted in a significant (P<0.01) improvement in each of daily feed intake, daily weight gain, testosterone hormone, and γ-globulin and a significantly (P<0.01) reduced glucose, cholesterol fraction levels in comparison to the control group. Additionally, adding clove oil increased (P<0.01) the rabbit bucks' physical semen attributes values. It was determined that including clove oil in the diet of male rabbits improved physiological body processes, produced hypercholesterolemia, and raised the quality of the rabbits' sperm without having a negative impact on liver or kidney function.